An exploration of initial purchase price dispersion and service-subscription duration - Lee, Seung Hwan (Sustainability (Switzerland), 2019)
Despite the readily available consumer price information, price dispersion persists for products and services and has been extensively researched. However, there is scant literature on the influence of price dispersion on consumer behavior. The present study uses actual consumer purchase data of software service subscriptions and applies range-frequency principles to investigate how a customer's price and relative position along a distribution at initial subscription might impact their subscription lifetimes. The study findings reveal that, in general, consumers paying higher initial prices retain their subscriptions longer, confirming the relationship between a consumer's service value expectation and search cost. However, the amount of a consumer's paid prices relative to that of other consumers' can be helpful in predicting subscription duration. Consumers paying a relatively high price compared with others with similar subscription beginning dates have shorter subscription durations, which raise a concern regarding use of individual customer's price information. The study suggests that principles of range-frequency theory are useful for comprehensively integrating price dispersion information. One interesting and counterintuitive implication of our analysis is that advantaged-price inequities (where the focal customer's paid price is lower compared to another customer's paid price) can also raise concerns about unfairness.
Keywords: Price dispersion; Price unfairness; Service duration; Social price comparison; Sustainable pricing